2015
DOI: 10.3892/mmr.2015.4710
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol protects mice from paraquat-induced lung injury: The important role of SIRT1 and NRF2 antioxidant pathways

Abstract: Abstract. Sirtuin 1 (SIRT1) acts via the deacetylation of a number of crucial transcription factors and has been implicated in various biological processes, including oxidative stress. Previous studies have indicated that nuclear factor, erythroid 2-like 2 (NRF2) is an effective target of antioxidant therapy for paraquat (PQ) poisoning. However, the association between SIRT1 and NRF2 and their effects in PQ-induced oxidative stress remains to be elucidated. The current study demonstrated that PQ exposure upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 22 publications
5
44
0
Order By: Relevance
“…It was founded that MA inhibited the expression of SIRT1 by inducing oxidative stress with elevated ROS levels, increased SOD and reduced GCS. MA‐induced lung toxicity is linked to oxidative injury by directly activating NAPDH oxidase and generating of ROS that cause cellular damages . Previous studies reported that MA increased ROS production in lungs, which are consistent with the results of the current study.…”
Section: Discussionsupporting
confidence: 93%
“…It was founded that MA inhibited the expression of SIRT1 by inducing oxidative stress with elevated ROS levels, increased SOD and reduced GCS. MA‐induced lung toxicity is linked to oxidative injury by directly activating NAPDH oxidase and generating of ROS that cause cellular damages . Previous studies reported that MA increased ROS production in lungs, which are consistent with the results of the current study.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, SIRT1 overexpression was associated with a high level of GSH, as well as SOD and CAT activities, the downstream genes of NRF2-anti-ARE, whereas the depletion of SIRT1 markedly increased the activity of MDA and HO-1, which suggested that SIRT1 protein may play an important role in mediating the oxidant-antioxidant balance in PQ-induced pulmonary injury (39) and enhanced cell resistance to oxidative stress. In a previous study of ours (40), resveratrol, an activator of SIRT1, increased the SIRT1 and NRF2 levels, and through the activation of the NRF2-ARE pathway led to the suppression of ROS production.. In that study, we demonstrated that PQ stimulated the compensatory overexpression of SIRT1 and NRF2, whereas exposure to PQ for a longer period of time significantly decreased the expression of SIRT1, as well as NRF2 in the lungs of mice.…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies reported that Nrf2 can be activated or inhibited upon stress conditions. For example, Nrf2 mRNA and protein levels are increased at 6 and 24 hr after paraquat administration but are decreased at 72 hr (Li et al, ). In human umbilical vein endothelial cells, 50–100 μg/ml PM2.5 elevated the level of Nrf2, whereas a decreased expression of Nrf2 was observed at 200–400 μg/ml PM2.5 (Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of resveratrol against oxidative stress can be mediated through an Nrf2‐dependent mechanism (Canella et al, ; Li et al, ). Our results illustrated that resveratrol alleviated PM2.5‐induced oxidative stress and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%